(untitled) - ARIFIN ZULKARNAIN, MOCHAMAD (Jurnal Ilmu Manajemen (JIM), 2018)
Togamas Petra Surabaya bookstore has implemented a vigorous sales promotion and provides an attractive outlet display for customers to visit and shop in stores, but the bookstore has experienced a decreased number of visitors and buyers in the stores over the past few months. The purpose of this study is to analyze and discuss the influence of sales promotion and store atmosphere towards purchase decision on Togamas Petra Surabaya bookstore. This type of research is conclusive research with quantitative approach. The population in this study is the visitors who purchased books at the Togamas Petra Surabaya bookstore that has a minimum age of 18 years old. Using non probability sampling as a sampling method is and purposive sampling as a sampling technique. 210 sample was used. The data analysis technique use multiple linear regression with SPSS program for windows 23. The results of this study indicate that sales promotion variables do not affect the purchase decisions of Togamas Petra Surabaya bookstore and store atmosphere has influenced the purchasing decisions on Togamas Petra Surabaya bookstore. keywords: Sales promotion , store atmosphere, purchase decision.